Wyszukiwarka Google jako praktyczne narzędzie lingwistyczne do opisu innowacyjnych użyć frazeologizmów - Dziamska-Lenart, Gabriela; Woźniak-Wrzesińska, Ewelina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
The aim of this article is to present the basic capabilities of the Google search engine in the process of analysing multi-word lexical combinations. Our assumption is that the Google search engine can be regarded as a kind of linguistic database ready to be used as a practical linguistic tool. The text is an overview, therefore the presented material is limited to the necessary minimum, i.e. fifty randomly-selected phraseological compounds. In the introduction, we list ( and briefly discuss ) the tools available for studying Polish-language multi-word lexical combinations. With such an outlined background, we may characterise the Google search engine as a linguistic database. Finally, in the relevant part, we present the ways of using this tool with selected examples. In the summary, we discuss the possibilities offered by the use of a constantly-updated linguistic database which the Internet search engine under review can be considered to be.